Spiritual vegetation: vegetal nature in religious contexts across medieval and early modern Europe - Lamsechi, Guita; Trînca, Beatrice; Petry, Tobias (Berliner Mittelalter- und Frühneuzeitforschung, 2022)
This volume concerns premodern understandings of vegetal nature that encompass multiple semantics and perspectives. Scholars from the disparate fields of art history, literature, and religious studies present tantalizing studies of trees and plants in sacred and secular thought. Some discuss the concept of the Book of Nature and its implications. Others explore narratives of symbiosis between humans and vegetal material, tree-dwelling hermits, spirits metamorphosing into wood, flowers or trees that sprout from bodies or the dissolution of the self into the natural world. Complementary to these approaches are studies that suggest a collapsing of time and space in spiritually charged yet ambiguous natural motifs or topographies where forests or groves are spaces of transformative experience.
Keywords: Konferenzschrift -- 2015 -- Berlin; Christliche Kunst; Pflanzensymbolik; Pflanzendarstellung; Naturdarstellung; Geschichte 500-1700; Kultur; Christentum; Spiritualität; Pflanzen